Strategi Pembelajaran Matematika Awal untuk Anak Usia Dini Kelompok A Usia 4-5 Tahun Melalui Permainan Tradisional Congklak di TK PKK Ngadireso: Early Mathematics Learning Strategies for Early Childhood (Group A, Ages 4–5) Using the Traditional Game of Congklak at PKK Ngadireso Kindergarten - Kamilia Masluchah; Rina Wijayanti; Henny Anggraini (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2026)
Early mathematics learning for young children requires strategies that are appropriate to their stage of cognitive development, namely through concrete experiences and play-based activities. This study aims to improve the early mathematics abilities of Group A early childhood students (aged 4–5 years) through the implementation of the traditional game congklak at TK PKK Ngadireso, Malang Regency. The study employs a qualitative approach using Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects consisted of 11 children. Data collection techniques included observation, interviews, and documentation, while data analysis was carried out descriptively and qualitatively. The results indicate that children’s early mathematics abilities showed a significant improvement after the implementation of learning strategies through the congklak game. The average level of children’s early mathematics ability increased from 42.00% in the pre-action stage to 58.40% in Cycle I and rose significantly to 86.40% in Cycle II. In addition to enhancing cognitive aspects, the congklak game also had a positive impact on children’s enthusiasm, active participation, and ability to follow game rules. Therefore, it can be concluded that the traditional congklak game is effective as a learning strategy to improve early mathematics abilities in early childhood.   ABSTRAK Pembelajaran matematika awal pada anak usia dini memerlukan strategi yang sesuai dengan tahap perkembangan kognitif anak, yaitu melalui pengalaman konkret dan kegiatan bermain. Penelitian ini bertujuan untuk meningkatkan kemampuan matematika awal anak usia dini kelompok A (usia 4–5 tahun) melalui penerapan permainan tradisional congklak di TK PKK Ngadireso, Kabupaten Malang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Setiap siklus terdiri atas tahapan perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian berjumlah 11 anak. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi, sedangkan analisis data dilakukan secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa kemampuan matematika awal anak mengalami peningkatan yang signifikan setelah diterapkan strategi pembelajaran melalui permainan congklak. Rata-rata kemampuan matematika awal anak pada pra tindakan sebesar 42,00%, meningkat menjadi 58,40% pada Siklus I, dan meningkat secara signifikan menjadi 86,40% pada Siklus II. Selain meningkatkan aspek kognitif, permainan congklak juga berdampak positif terhadap antusias, keterlibatan aktif, serta kemampuan anak dalam mengikuti aturan permainan. Dengan demikian, dapat disimpulkan bahwa permainan tradisional congklak efektif digunakan sebagai strategi pembelajaran untuk meningkatkan kemampuan matematika awal anak usia dini.